Comparison of two disk diffusion and E-test methods in determining antibiotic susceptibility of Pseudomonas aeruginosa strains in isolated burn infections of Ahvaz City (Bangladesh Journal of Medical Science, 2020)
Background: Pseudomonas aeruginosa with widely distributed in nature, for human beings is considered an opportunistic pathogen that causes infections of broad-spectrum, including administrative, respiratory, septicemia and bacteremia and sepsis in patients with the burning city of Ahvaz.Method and Material: A total of 95isolates of Pseudomonas aeruginosa isolated from burn patients from January 2015 assemble and biochemical identification test, then they are antibiotic resistance in E. test and disk diffusion method were compared.Findings: From 95 different clinical isolates of Pseudomonas aeruginosa isolated from E. test with the highest sensitivity to the antibiotic ceftazidime , 70(68/73%) and ciprofloxacin 50 (63/52%) and gentamicin 48 (52 /50 %) and the antibiotic imipenem 44 (31/46%) were sensitive and disk diffusion method antibiotic ceftazidime, 67(52/70%) and the antibiotic Ciprofloxacin 51(68/53%) and safety antibiotic imipenem 49(57/51%) and gentamicin 48(52/50%) were sensitive.Conclusion: Statistically significant differences between E. test and disk diffusion antimicrobial susceptibility of there (p